Functional heterogeneity in senescence - Kirschner, Kristina; Rattanavirotkul, Nattaphong; Quince, Megan F; Chandra, Tamir (Biochemical Society transactions, 2020)
Senescence is a tumour suppressor mechanism which is cell-intrinsically activated in the context of cellular stress. Senescence can further be propagated to neighbouring cells, a process called secondary senescence induction. Secondary senescence was initially shown as a paracrine response to the secretion of cytokines from primary senescent cells. More recently, juxtacrine Notch signalling has been implicated in mediating secondary senescence induction. Primary and secondary senescent induction results in distinct transcriptional outcomes. In addition, cell type and the stimulus in which senescence is induced can lead to variations in the phenotype of the senescence response. It is unclear whether heterogeneous senescent end-points are associated with distinct cellular function in situ, presenting functional heterogeneity. Thus, understanding senescence heterogeneity could prove to be important when devising ways of targeting senescent cells by senolytics, senostatics or senogenics. In this review, we discuss a role for functional heterogeneity in senescence in tissue- and cell-type specific manners, highlighting potential differences in senescence outcomes of primary and secondary senescence.